Knowledge Translation in a Community-Based Study of the Relations Among Violence Exposure, Post-traumatic Stress and Alcohol Misuse in Mi’kmaq Youth - Zahradnik, Marc; Stewart, Sherry; Stevens, Doreen; Wekerle, Christine (First Peoples Child & Family Review, 2009)
In 2004, our research group was invited to continue a research partnership with a Nova Scotian Mi’kmaq community that was concerned about the causes of and interventions for adolescent alcohol misuse in their community. While our previous collaborative research focused on reducing adolescent alcohol misuse by targeting motivations for drinking that were personality specific (see Mushquash, Comeau, & Stweart, 2007), the more recent collaboration sought to investigate the possible relationship between exposure to violence, post-traumatic stress, and alcohol misuse. The present paper outlines the steps involved in gaining community consent, the plan for results sharing, the tangible benefits to the community that have been documented, and future directions and lessons learned. The paper will demonstrate how the principles of Knowledge Translation (CIHR, 2006) provide a framework for this process.